Drimane-type compounds in source rocks and fluids from fluvial-deltaic depositional settings in the North-West Shelf of Australia - Cesar, J.; Grice, Kliti (Pergamon, 2018)
Fluvial-deltaic petroleum systems with gas-prone source rocks are difficult to assess because the released fluids generally lack biomarkers and this limits the implementation of traditional organic geochemistry screening. However, there are a number of compound classes yet to be investigated in order to establish novel parameters for correlation studies in fluvial-deltaic geological settings. In this study we have focused on drimane-skeleton molecules (C15-decalins), particularly the compounds 1,2,2,5,5-pentamethyl-trans-decalin and 1,1,2,5,5-pentamethyl-trans-decalin (termed herein as rearranged drimanes RD1 and RD2, respectively) and drimane (D), in source rock extracts and fluids from fluvial-deltaic petroleum systems in the Carnarvon Basin, North-West Shelf of Australia (NWS). We have calculated the ratio (RD1 + RD2)/D as proposed by Ji et al. (Ji, L., He, C., Zhang, M., Wu, Y., Li, X. [2016]. Bicyclic alkanes in source rocks of the Triassic Yanchang Formation in the Ordos Basin and their inconsistency in oil-source correlation. Marine and Petroleum Geology 72, 359–373) and compared their results with samples from the NWS. Our compilation of rearranged drimane ratios for a variety of lithologies suggests clay-catalysed rearrangement of C15-decalins in siliciclastic source rocks from fluvial-deltaic depositional environments. Therefore, the mineral content seems to be a key factor controlling the isomerisation of decalins. Samples with higher clay content, such as claystone from the Brigadier Formation, have higher (RD1 + RD2)/D ratios (∼6) and higher C29 diasterane/C29 sterane (∼1.1) compared to silty claystone from the Legendre Formation (∼2 and ∼0.8 respectively). The effects exerted by thermal maturity of the source rock and redox conditions of the depositional environment require further investigation, although samples from the Yanchang Fomation and La Luna Formation, where deposition occurred under more reducing conditions, exhibit lower rearranged drimane ratios (< 2).